Human Capital and How It Affects the Performance of an Organization - Rahmikawati Rahmikawati; Nelly Nelly; Susanti Susanti; Nurfiani Syamsuddin; Arsyad Arsyad (International Conference on Multidisciplinary Research, 2022)
Many countries' economies collapsed in early 2020 due to the worldwide financial crisis and the Covid 19 pandemic. The economic stability of several nations has been disrupted by the outbreak. In this article, we will examine the many ways in which human capital contributes to a company's success. The administration is making significant efforts to boost economic growth in a more positive direction. The Human Development Index in Indonesia appears to have increased by 3.3% between 2015 and 2019, according to data from UNDP 2020. According to the Human Development Index (HDI), Indonesia would be ranked 107 out of 189 countries in 2020. The Indonesian government has taken many different ways and made many different kinds of attempts to help its people grow and develop their skills so that they can keep competing with other nations. The companies discussed here also played a role in spurring this expansion. Organizations in the business world also want to survive, thrive, and remain competitive on a global scale. Businesses have a responsibility and a potential remedy to their lack of global competitiveness: they can stimulate the growth of their resources. The best way for businesses to improve their performance is to invest wisely and train their employees further. The success of businesses can be directly attributed to their investment in human capital. Human capital models that explain why it matters for businesses to invest in their people have been backed up by this research. Keywords: Human Development Index, A Sustainable and Globally Competitive Economy